REFLECTIONS ON THE KEYNES’ METHOD - Bittes Terra, Fábio Henrique; Ferrari Filho, Fernando (Revista Venezolana de Análisis de Coyuntura, 2018)
As we know, some authors argue that Keynes adopted the historical-deductive method in hismain writings, while others argue that the logical and inductive methods are found in his works.Given that, first, the paper presents, briefly, the literature on Keynes’ method, based on Carabelli(1988), O’Donnell (1989) and Carvalho (1992), among others. Second, considering Keynes’thoughts related to the logical and induction in his Treatise on Probability, the paper exploreshow his insights in this book appear in his most important economic books, namely A Tract onMonetary Reform, Treatise on Money and The General Theory of Employment, Interest andMoney.